Transnationalization of production enterprises of confectionary markets - Zharikov, Andriy; Batchenko, Liudmyla (Skhid, 2013)
In this article is classified world confectionary markets in terms of investment attractiveness, is justified the choice of countries, which are the most appropriate for production enterprise creation, is calculated the potential growth level of network spread index and transnationalization index for one of the leading companies on the Ukrainian confectionary markets under the condition of enterprises establishment in the mentioned regions of the world.